2014
DOI: 10.1186/1475-2891-13-78
|View full text |Cite
|
Sign up to set email alerts
|

Maternal low glycaemic index diet, fat intake and postprandial glucose influences neonatal adiposity – secondary analysis from the ROLO study

Abstract: BackgroundThe in utero environment is known to affect fetal development however many of the mechanisms by which this occurs remain unknown. The aim of this study was to examine the association between maternal dietary macronutrient intake and lifestyle throughout pregnancy and neonatal weight and adiposity.MethodsThis was an analysis of 542 mother and infant pairs from the ROLO study (Randomised cOntrol trial of LOw glycaemic index diet versus no dietary intervention to prevent recurrence of fetal macrosomia).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 59 publications
2
35
1
Order By: Relevance
“…Another limitation is that not all women participated in the hyperinsulinemic-euglycemic clamp portion of the study; therefore, this might have reduced our power to detect differences in lean women from the obese groups during hyperinsulinemia. We also did not assess postprandial lipid and glucose metabolism, where in a previous study, it has been shown to correlate with infant adiposity (47). We also did not measure maternal body composition to which glucose and lipid kinetics could have been normalized.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that not all women participated in the hyperinsulinemic-euglycemic clamp portion of the study; therefore, this might have reduced our power to detect differences in lean women from the obese groups during hyperinsulinemia. We also did not assess postprandial lipid and glucose metabolism, where in a previous study, it has been shown to correlate with infant adiposity (47). We also did not measure maternal body composition to which glucose and lipid kinetics could have been normalized.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of skinfold thickness measures was obtained by adding all of the obtained skinfold thickness measurements together, and a ratio of abdominal circumference to length calculated as an indicator of central adiposity. 25 Fat mass and fat free mass were calculated based on infant sex, weight, and triceps, subscapular and thigh skinfold thicknesses (as described below). Fat free mass was also determined using bio-impedance analysis (BIA).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, we did not find a significant association between dietary total lipid and saturated and polyunsaturated fatty acids intake with LGA newborns. Other studies have found an association between cholesterol dietary intake (Campos, Pereira, Queiroz, & Saunders, ), maternal dietary fat intake (Horan, McGowan, Gibney, Donnelly, & McAuliffe, ) and a lipid‐based nutritional supplement intake (Adu‐Afarwuah et al, ) and a newborn's anthropometric measurements and fetal growth as measured by birth weight and BMI‐for‐age z ‐scores. According to Kulkarni et al (), data from the Pune Maternal Nutrition Study revealed that the cholesterol concentrations at both 18 and 28 gestational weeks were positively associated with the newborn birth size.…”
Section: Discussionmentioning
confidence: 95%
“…The association between higher energy and fat intake during pregnancy with birth weight is not completely understood (Rao et al, ; Lagiou et al, ; Godhia, Nigudkar, & Desai, ), and further questions arise. Some studies (Kulkarni et al, ; Horan et al, ; Ye et al, ) suggest that dietary fat intake and maternal lipid profile levels could be linked to the newborn birth weight. Studies also reported a positive association between animal fat intake during the second trimester of pregnancy and newborn birth size (Weigel, Nárváez, López, Félix, & López, ) as well as a positive association between the percentage of maternal energy intake from saturated fat in late pregnancy and neonatal central adiposity (Lagiou et al, ).…”
Section: Discussionmentioning
confidence: 99%